2014
DOI: 10.1071/ah13050
|View full text |Cite
|
Sign up to set email alerts
|

Successful provision of emergency mental health care to rural and remote New South Wales: an evaluation of the Mental Health Emergency Care–Rural Access Program

Abstract: Objective. To evaluate a rural emergency telepsychiatry program, the Mental Health Emergency Care-Rural Access Program (MHEC-RAP), which aims to improve access to emergency mental health care for communities throughout western New South Wales (NSW).Methods. A descriptive analysis of service activity data from the introduction of the MHEC-RAP in 2008 to 2011 using Chi-squared tests and linear regression modelling to assess change and trends over time.Result. There were 55 959 calls to the MHEC-RAP, 9678 (17%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
1
30
0
Order By: Relevance
“…A second approach is use of telemedicine or teleconsultation to link inexperienced providers with mentors to help navigate buprenorphine OMT procedures. These approaches are becoming more widely used in general medicine (Biery, Bond, Smith, LeClair, & Foster, 2015; Eaton et al, 2015; Gillis, 2015; Khan et al, 2015; Marcolino, Pereira Afonso Dos Santos, Santos Neves, & Alkmim, 2015), have been associated with reductions in medical errors or referrals to formal treatments (Campanella et al, 2015), and have particular value for remote or rural areas (Saurman, Lyle, Perkins, & Roberts, 2014) for which research has indicated there is a dearth of available opioid treatment options (Blum et al, 2016; Cunningham et al, 2007; Jones et al, 2015; Knudsen et al, 2005; Knudsen, 2015). The Physician Clinical Support System-Buprenorphine(PCSS-B) is a federally funded program that is already in place to pair newly waivered physicians with an experienced provider usually via telephone or email, but possibly with in-person meetings as well (Egan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A second approach is use of telemedicine or teleconsultation to link inexperienced providers with mentors to help navigate buprenorphine OMT procedures. These approaches are becoming more widely used in general medicine (Biery, Bond, Smith, LeClair, & Foster, 2015; Eaton et al, 2015; Gillis, 2015; Khan et al, 2015; Marcolino, Pereira Afonso Dos Santos, Santos Neves, & Alkmim, 2015), have been associated with reductions in medical errors or referrals to formal treatments (Campanella et al, 2015), and have particular value for remote or rural areas (Saurman, Lyle, Perkins, & Roberts, 2014) for which research has indicated there is a dearth of available opioid treatment options (Blum et al, 2016; Cunningham et al, 2007; Jones et al, 2015; Knudsen et al, 2005; Knudsen, 2015). The Physician Clinical Support System-Buprenorphine(PCSS-B) is a federally funded program that is already in place to pair newly waivered physicians with an experienced provider usually via telephone or email, but possibly with in-person meetings as well (Egan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Program efficiency was estimated for the study period (to compare AM and PM shifts) and for a 12 month period using 2011 activity data which was previously collected for the evaluation [27,28]. These data were summarized graphically and used medians because data were skewed.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluation findings have already been reported on service activity and program reach [27,28]. The decision to fund the program represents an opportunity cost that needs to be considered both in terms of improved access to specialist services and program efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…One Canadian demonstration project connecting older adults with a university-related psychogeriatric service improved the referring team's knowledge base and subsequent ability to construct better treatment plans for patients [8]. In Australia, one statewide health department has demonstrated that telehealth can successfully provide emergency mental health care for rural communities [9]. There has been significant progress in developing funding models to accommodate changes to clinical practice caused by telehealth by reimbursements for time and subsidies for infrastructure setup for providers [10,11].…”
Section: Introductionmentioning
confidence: 98%